2021
DOI: 10.1113/jp281800
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral impairments of oxidative metabolism after a 10‐day bed rest are upstream of mitochondrial respiration

Abstract: The peer review history is available in the supporting information section of this article (https://doi.org/10.1113/JP281800#support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…After having checked that the TSI signal following VOT returned to baseline values (~ 5 min), skeletal muscle oxidative capacity was evaluated in vivo by measuring post-exercise muscle oxygen consumption ( m V̇O 2 ) recovery kinetics by NIRS and the repeated occlusions method 16 , 17 . The protocol consisted of a 3-min rest followed by a 10-min moderate intensity (~ 50% V̇O 2peak ) constant work rate exercise bout aiming to increase m V̇O 2 and desaturate the muscle to ~ 50% of A TSI (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…After having checked that the TSI signal following VOT returned to baseline values (~ 5 min), skeletal muscle oxidative capacity was evaluated in vivo by measuring post-exercise muscle oxygen consumption ( m V̇O 2 ) recovery kinetics by NIRS and the repeated occlusions method 16 , 17 . The protocol consisted of a 3-min rest followed by a 10-min moderate intensity (~ 50% V̇O 2peak ) constant work rate exercise bout aiming to increase m V̇O 2 and desaturate the muscle to ~ 50% of A TSI (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…In health, skeletal muscle oxidative capacity is strongly correlated with whole body aerobic capacity and exercise performance (Holloszy, 1967;Hood et al, 2011;Hoppeler et al, 1985). Moreover, muscle oxidative capacity and mitochondrial function are impaired in conditions of physical inactivity (Buso et al, 2019;Zuccarelli et al, 2021), aging (Layec et al, 2013) and chronic disease, such as obesity (Lazzer et al, 2013;Menshikova et al, 2005), diabetes (Joseph et al, 2012) myopathy (Grassi et al, 2019(Grassi et al, , 2020, pulmonary obstructive disease (Adami et al, 2017(Adami et al, , 2020 and neuromuscular disease (Breuer et al, 2013). Traditionally, muscle oxidative capacity has been studied using ex vivo approaches involving muscle biopsy samples and measurement of enzyme activity or mitochondrial respiratory capacity in isolated mitochondrial preparations and permeabilized muscle fibres (Brand & Nicholls, 2011;Chance & Williams, 1955;Gnaiger, 2009;Holloszy, 1967;Perry et al, 2013).…”
Section: Nirs and Muscle Oxidative Capacitymentioning
confidence: 99%
“…Female were excluded from the study to avoid confounding physiological conditions related to the menstrual cycle. Participants’ body mass and body mass index estimated in pre and post bed rest conditions in a parallel study revealed a slight but significant decrease ( Zuccarelli et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%